Analisis Peran Keterlibatan Ayah dalam Mengoptimalkan Perkembangan Kognitif, Sosial-Emosional, dan Bahasa Anak Usia Dini - Novita, Della; Nasution, Riskha Hanifa (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the impact of father involvement on various aspects of early childhood development, including cognitive, socio-emotional, language, and moral development. The main issue raised is the still low level of father participation in childcare, which tends to be dominated by mothers, thus potentially hindering optimal child development. The method used in this study is a qualitative approach with a literature study type, through data collection from various scientific journals, books, and relevant previous research results. Data analysis techniques are carried out through data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the active involvement of fathers in parenting has a significant positive influence on child development, especially in increasing self-confidence, social skills, emotional regulation, and language development. In addition, the presence of fathers also contributes to the formation of character and moral values of children from an early age. The conclusion of this study confirms that the role of fathers is an important factor in supporting holistic and sustainable child development. Therefore, awareness and joint commitment from families are needed to increase father involvement in the early childhood care process.